Ethyl‐N‐dodecanoyl‐l‐arginate hydrochloride combats pathogens with low‐resistance generation by membrane attack and modifies gut microbiota structure. Issue 3 (22nd November 2019) - Shao, Ting; Fan, Tingting; Tang, Wenshu; Sun, Yanting; Gao, Song; Chen, Huang; Sun, Zhenliang; Liu, Mingyao; Yi, Zhengfang
Summary: Ethyl‐ N ‐dodecanoyl‐l ‐arginate hydrochloride (LAE, ethyl lauroyl arginate HCl) is a cationic surfactant used as a food preservative with broad‐spectrum antibacterial activities. However, its resistance development, influences on gut microbiome and molecular target are unclear. In this study, bacteria were stimulated by LAE for 30 days to test the bacterial resistance. Several infected animal models were used to evaluate the antibacterial effect of LAE in vivo . Mice were orally treated with LAE to test its effect on animal growth. The influence of LAE on mice gut microbiome was analysed by 16S rDNA sequencing. The results indicated that Escherichia coli did not develop resistance to LAE. LAE significantly combats bacterial infection in mice, ducklings and piglets. Moreover, LAE promotes mouse weight gain without changing body composition or reducing animal vitality, and induces lower hepatotoxicity than ampicillin. In the mouse gut microbiome assessment and characterization, LAE modifies host gut microbiota structure. Mechanistically, LAE specifically binds to acidic phospholipids including phosphatidylserine, depolarizes the membrane and disrupts the bacterial membrane followed by bacterial growth inhibition. This study investigates the molecular mechanism of LAE as well as its antibacterial functions in poultry and livestock. Our data suggest LAE is a potential antibacterial agent in animal health. Abstract : LAE binds to acid phospholipids and depolarizes the bacterial membrane resulting in bacterial death with low drug resistance. LAE exhibits antibacterial activity in vivo and promotes growth with potentially beneficial modifications to the gut microbiota. As a result, LAE is not only a potential veterinary drug for bacterial infection but also a potential low‐risk feed additive for animal growth.